(untitled) (Bangladesh Journal of Child Health, 2010)
Objectives: The study was done to find out the relationship between constipation and urinary tract infection (UTI) in children. Methods: The study was a case control study between two groups in a tertiary care children hospital in Dhaka city. In group-1 (n=45) those children having history of constipation and in group-2 (n=78) as a control group having no history of constipation were included in this study. Growths of a single species of organism with colony count of >105/ml in a clean-catch midstream single urine sample was considered as evidence of urinary tract infection. Results: Positive urine culture was found in 8.9% (4/45) cases in children who had history of constipation and 1.3% (1/78) in children who had no history of constipation. Though the number of positive urine culture was seven times more in children with constipation than those who were not constipated but the difference between the two groups was not statistically significant (p=0.059) . Conclusion: Culture documented UTI in children with constipation is seven times more than without constipation showing impact of constipation on urinary tract infection (UTI) in children. Key words: Urinary tract infection (UTI); constipation. DOI: 10.3329/bjch.v34i1.5697 Bangladesh Journal of Child Health 2010; Vol.34(1): 17-20